2018
DOI: 10.22159/ijap.2017.v9s2.38
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Mothers’ Nutritional Status to Primary Teeth Dental Caries

Abstract: Methods:In total, 281 children under 5-year-old were selected from a health screening in Depok Sub-District, West Java. Information about maternal nutritional status was collected through the mother and child's health book. Information about dental caries was collected through clinical examinations using the dmft index. Result:The prevalence of mothers with poor nutritional status was 22.8%, and 55.2% of their children had caries. The occurrence of dental caries in primary dentition between children of mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…9 It was reported that a mother's nutrition during pregnancy is directly related to the primary teeth eruption of her offspring. 22 Through thymoquinone therapy, delayed eruption can be prevented because thymoquinone is an antioxidant that can protect pancreatic β cells by decreasing oxidative stress and increasing the production of endogenous antioxidants in the body, such as glutathione peroxidase, superoxide dismutase and catalase, and improve metabolic disorders that cause malnutrition of proteinenergy in the fetus. 22,23 In diabetic pregnant rats, metformin therapy can improve insulin sensitivity because it improves blood glucose levels, and developmental tooth disorders can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…9 It was reported that a mother's nutrition during pregnancy is directly related to the primary teeth eruption of her offspring. 22 Through thymoquinone therapy, delayed eruption can be prevented because thymoquinone is an antioxidant that can protect pancreatic β cells by decreasing oxidative stress and increasing the production of endogenous antioxidants in the body, such as glutathione peroxidase, superoxide dismutase and catalase, and improve metabolic disorders that cause malnutrition of proteinenergy in the fetus. 22,23 In diabetic pregnant rats, metformin therapy can improve insulin sensitivity because it improves blood glucose levels, and developmental tooth disorders can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Teeth are the strongest and strongest calcified body structures, but their formation is highly dependent on the influence of diet and metabolism of the fetus and immediately after birth. During pregnancy, the mother's health is as vital as the continuity of the formation of teeth ( 17 ).…”
Section: Linking Fetal Undernutrition That Yields To Neonatal Stuntin...mentioning
confidence: 99%
“…Intrauterine malnutrition can affect the growth and development of various organs in the child's body, including the growth and development of teeth. Although malnourished children often experience delayed tooth eruption, dental caries are very high in early childhood, especially when malnutrition occurs during tooth formation ( 17 ). Growth stunting children in Indonesia have experienced primary caries, and most of them are of high severity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Sejalan dengan hasil penelitian Tanaka et al 21 di Jepang yang melaporkan hubungan antara asupan vitamin D ibu yang lebih tinggi selama kehamilan dan pengurangan risiko karies gigi pada anak. Penelitian oleh Badruddin et al 22 di Kota Depok menunjukkan terdapat hubungan bermakna antara status gizi ibu saat kehamilan dengan karies gigi sulung pada anak (p<0,001). Oleh karena itu, malnutrisi termasuk defisiensi makronutrien dan mikronutrien pada ibu hamil akan memengaruhi integritas gigi sulung anak kelak.…”
Section: Bahasanunclassified